Development of Monopoly Wordwall Media to Enhance English Vocabulary Mastery in Elementary School - Nikmatul Chasanah Tarasti; Sigit Yulianto (AL-ISHLAH: Jurnal Pendidikan, 2025)
Game-based learning media integrates game elements with educational objectives, offering an engaging and enjoyable learning experience. This study aimed to (1) develop Mowall-based interactive media for English language learning, (2) evaluate its feasibility, and (3) assess its effectiveness for fourth-grade students. The research employed a Research and Development (RD) design based on the Borg and Gall model. The participants were fourth-grade students from SDN Wonosari 02, Semarang City. Data were collected using interviews, documentation, needs and response questionnaires, validation sheets, and pretest-posttest instruments. Data analysis involved normality tests, paired-sample t-tests, and N-gain calculations. Validation results indicated high feasibility of the media: 96.9% from media experts, 95% from material experts, and 86.7% from language experts. Normality tests showed that pretest and posttest data were normally distributed (small-scale: 0.773 and 0.090; large-scale: 0.635 and 0.112). Paired t-test results showed significant improvement in student performance (small-scale: p = 0.003; large-scale: p = 0.000, both p 0.005). N-gain scores were 0.35 (small-scale) and 0.53 (large-scale), both indicating moderate effectiveness. In conclusion, the Mowall interactive media is both feasible and moderately effective in improving English learning outcomes among fourth-grade students.